2021
DOI: 10.15740/has/ijas/17-aaebssd/79-86
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of eco-friendly mountages for the silkworm, Bombyx mori L.

Abstract: The silkworm Bombyx mori L. ends its larval stage with construction of silken armour called ‘cocoon’. The management of spinning larvae demands much care to maximize profit to the farmer, which necessitates manual picking of the ripened worms and provide proper anchorage to construct cocoons and the process is called as mounting. More than 40 % of the labour force is dedicated towards mounting (15 out of total 35 mandays/100 DFLs) that draws attention of the researchers striving hard to double farmer’s income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(5 reference statements)
0
0
0
Order By: Relevance
“…Similar results were reported from Vinoda et al (2021) where they reported that higher number of larvae from selfmounting spiral mountage when compared to plastic collapsible mountage among self-mounting structures. The intricately woven bamboo spiral mountage might have provided better anchorage for the silkworm to crawl when compared to plastic collapsible mountage allowing a greater number of larvae on the self-spiral mountage.…”
Section: Resultssupporting
confidence: 87%
“…Similar results were reported from Vinoda et al (2021) where they reported that higher number of larvae from selfmounting spiral mountage when compared to plastic collapsible mountage among self-mounting structures. The intricately woven bamboo spiral mountage might have provided better anchorage for the silkworm to crawl when compared to plastic collapsible mountage allowing a greater number of larvae on the self-spiral mountage.…”
Section: Resultssupporting
confidence: 87%